Competition and efficiency in congested markets - Acemoglu, Daron 1967-; Ozdaglar, Asuman E. (National Bureau of Economic Research, 2005)
"We study the efficiency of oligopoly equilibria in congested markets. The motivating examples are the allocation of network flows in a communication network or of traffic in a transportation network. We show that increasing competition among oligopolists can reduce efficiency, measured as the difference between users' willingness to pay and delay costs. We characterize a tight bound of 5/6 on efficiency in pure strategy equilibria. This bound is tight even when the number of routes and oligopolists is arbitrarily large. We also study the efficiency properties of mixed strategy equilibria"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Competition -- Econometric models; Oligopolies